2019
DOI: 10.7341/20191521
|View full text |Cite
|
Sign up to set email alerts
|

The impact of self-employment on the economic integration of immigrants: Evidence from Germany

Abstract: Traditi onal approaches in migrati on studies suggest that self-employment and entrepreneurial acti viti es enhance the perspecti ves of economic advancement of immigrants in host countries. Therefore, in many popular desti nati ons in Western Europe and Northern America, policies encouraging the self-employment of immigrants have been proposed. But does the self-employment contribute to the economic integrati on of immigrants? Is it a universal, one-way avenue that guarantees the successful inserti on of fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 27 publications
0
9
0
4
Order By: Relevance
“…Moreover, the study suggests that migrants improve their well-being by participating more frequently in socio-cultural activities, even though their average reported well-being is lower than natives. Overall, there is an extensive body of research on the economic integration of immigrants, including wages, employment and occupations, full-time employment, participation in welfare programs, and burden to public finances (Algan et al, 2010; Akdede & Giovanis, 2020; Borjas, 1995, 2002; Brzozowski & Lasek, 2019; Green, 1999; Riphahn, 2004). Moreover, numerous studies explored the dimensions of socio-cultural integration, such as migrants’ perception of ethnic or national identity, socialization, fertility, and citizenship acquisition (Blau, 1992; Bueker, 2005; Constant et al, 2009; Dustmann, 1996; Manning & Roy, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, the study suggests that migrants improve their well-being by participating more frequently in socio-cultural activities, even though their average reported well-being is lower than natives. Overall, there is an extensive body of research on the economic integration of immigrants, including wages, employment and occupations, full-time employment, participation in welfare programs, and burden to public finances (Algan et al, 2010; Akdede & Giovanis, 2020; Borjas, 1995, 2002; Brzozowski & Lasek, 2019; Green, 1999; Riphahn, 2004). Moreover, numerous studies explored the dimensions of socio-cultural integration, such as migrants’ perception of ethnic or national identity, socialization, fertility, and citizenship acquisition (Blau, 1992; Bueker, 2005; Constant et al, 2009; Dustmann, 1996; Manning & Roy, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study conducted in the United States found that minority entrepreneurs with prior entrepreneurial experience had better access to funds from financial institutions than minority entrepreneurs with little prior entrepreneurial experience [72]. A study conducted in Germany found that immigrant entrepreneurs with previous self-employment experience were less integrated in the market than the average entrepreneur [73]. However, another study from the United States found that prior entrepreneurial experience increased the chances of an entrepreneur starting a new business due to expertise in spotting opportunities [74].…”
Section: Entrepreneurial Experiencementioning
confidence: 99%
“…However, by reviewing the current official information, data about entrepreneurial migrants is almost inexistent. In this regard, the Global Entrepreneurship Monitor (GEM) and the Panel Studies of Entrepreneurial Dynamic (PSED) projects have contributed with insights to understanding the phenomenon of entrepreneurial migrants by introducing special questions or matching with the official statistics about migration (see Li et al, 2018;Brzozowski & Lasek, 2019;Ashourizadeh & Wickstrøm, 2020). Likewise, the research community that studies entrepreneurial migrants has made efforts to generate empirical evidence of this phenomenon by collecting qualitative data (e.g., cases, interviews, narratives, ethnographies) and quantitative data (e.g., surveys).…”
Section: External Migrantmentioning
confidence: 99%